2017
DOI: 10.1074/jbc.m116.764985
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mammalian Glycoprotein YKL-40

Abstract: YKL-40 is a mammalian glycoprotein associated with progression, severity, and prognosis of chronic inflammatory diseases and a multitude of cancers. Despite this well documented association, identification of the lectin's physiological ligand and, accordingly, biological function has proven experimentally difficult. YKL-40 has been shown to bind chito-oligosaccharides; however, the production of chitin by the human body has not yet been documented. Possible alternative ligands include proteoglycans, polysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 81 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…To gain insight into the molecular mechanistic basis of the tumor facilitative effect of CHI3L1 in GC, we sought to identify CHI3L1 interacting partners. Here, we speculated that CD44 may constitute a potential receptor for CHI3L1 as they have respectively been shown to bind hyaluronic acid (HA, as its receptor) [ 27 ] and hyaluronan (as the likely preferred physiological ligand) [ 28 ]. First, we examined the expression level of CHI3L1, CD44, and IL-13Rα2 in a panel of human GC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain insight into the molecular mechanistic basis of the tumor facilitative effect of CHI3L1 in GC, we sought to identify CHI3L1 interacting partners. Here, we speculated that CD44 may constitute a potential receptor for CHI3L1 as they have respectively been shown to bind hyaluronic acid (HA, as its receptor) [ 27 ] and hyaluronan (as the likely preferred physiological ligand) [ 28 ]. First, we examined the expression level of CHI3L1, CD44, and IL-13Rα2 in a panel of human GC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As hyaluronan constitutes the likely preferred physiological ligand of CHI3L1 [28] and CD44 functions as a hyaluronan receptor, we speculated that CD44 may thus be a potential CHI3L1 receptor as well. In the present study, by using co-IP and co-location assay in two GC cell lines, we confirmed that CHI3L1 binds to CD44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst we have not directly explored whether Ym1 influences collagen biosynthesis or degradation, our data suggests Ym1 may regulate collagen fibril formation by controlling the quantity of epithelia-derived RELMα. Interestingly YKL-40, a CLP expressed in humans that has strong functional similarities to murine Ym1, not only contains binding motifs for heparin and hyaluronan [57], major constituents of the extracellular matrix, but also for type I collagen [58]. Moreover, binding of YKL-40 to collagen was shown to alter collagen structure or behaviour in a way that prevented cleavage of fibrils and hence aided collagen stability [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…CLPs exhibit lectin properties and can bind to extracellular matrix components such as hyaluronan or proteoglycans and cell surface glycosaminoglycans. 26 The physiologic functions of CLPs are not entirely understood, but they appear to be involved in a plethora of biological processes, including tissue remodeling, inflammation, and regulation of the immune response. CHI3L1 or YKL-40 is by far the most described CLP because of its implication in diverse pathologic conditions.…”
Section: Human Chitinases: Genes Family Structure and Functionmentioning
confidence: 99%